2021
DOI: 10.1073/pnas.2017292118
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the selection of fillers in police lineups

Abstract: A typical police lineup contains a photo of one suspect (who is innocent in a target-absent lineup and guilty in a target-present lineup) plus photos of five or more fillers who are known to be innocent. To create a fair lineup in which the suspect does not stand out, two filler selection methods are commonly used. In the first, fillers are selected if they are similar in appearance to the suspect. In the second, fillers are selected if they possess facial features included in the witness’s description of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
90
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(101 citation statements)
references
References 23 publications
10
90
1
Order By: Relevance
“…In one of their two experiments they manipulated filler similarity relative to the suspect (i.e., using different fillers in target-present and -absent cases). Consistent with the original propositions of Luus and Wells (1991) and Wells et al (1993; see also Oriet & Fitzgerald, 2018)-that increasing filler similarity beyond matching to description risks affecting guilty but not innocent suspect identifications- Colloff et al (2021) reported a decrease in pAUC as filler similarity increased. They contrasted these results with a second experiment where filler similarity was manipulated relative to the target.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…In one of their two experiments they manipulated filler similarity relative to the suspect (i.e., using different fillers in target-present and -absent cases). Consistent with the original propositions of Luus and Wells (1991) and Wells et al (1993; see also Oriet & Fitzgerald, 2018)-that increasing filler similarity beyond matching to description risks affecting guilty but not innocent suspect identifications- Colloff et al (2021) reported a decrease in pAUC as filler similarity increased. They contrasted these results with a second experiment where filler similarity was manipulated relative to the target.…”
supporting
confidence: 72%
“…However, it is important to note that the (six) target replacements in target-absent cases were selected to represent the worst-case scenario for innocent suspects: being high in similarity to the targets and likely in need of high similarity fillers to protect them from being mistakenly confused with the target. Under these circumstances, increases in suspect-filler similarity would presumably be more likely to help protect an innocent suspect than if they were low in similarity to the target (i.e., both because a low similarity innocent suspect is less likely to be confused with the target and because increasing suspect-filler similarity would be unlikely to increase the fillers' similarity to the target)-a notion that was formalized in recent modeling conducted by Colloff et al (2021). Furthermore, Lucas et al (2021) flagged their manipulation of filler similarity as potentially protecting innocent suspects to a greater extent than would occur in real cases, as a result of filler similarity being manipulated relative to the targets in both target-present and -absent cases.…”
mentioning
confidence: 99%
“…To find out, I downloaded open data from OSF for five recent, large-N eyewitness lineup papers comprising 8 separate experiments and 22 unique experimental conditions (Akan et al, 2021;Colloff et al, 2018Colloff, Seale-Carlisle, et al, 2021;Colloff, Wilson, et al, 2021;Morgan et al, 2019) There are general trends in the distributions of ID proportions across confidence levels-a curvilinear relationship for culprit-absent suspect IDs and a positive trend for culpritpresent suspect IDs. Despite these trends (which generally align with our current understanding of confidence-accuracy relationships; Brewer et al, 2021), there is a decent amount of condition-to-condition variability (e.g., in the mid-confidence range for culpritabsent IDs and the high-confidence range for culprit-present IDs).…”
Section: Challenge 1: the Shape Of The Datamentioning
confidence: 99%
“…Thus, this effect POWE(R)OC 14 size readily translates to changes at the base data level required for ROC data simulation 3 . A graphical example of practical effect size application (using data from Colloff, Wilson et al, 2021) is shown below in Figure 4.…”
Section: Challenge 2: Effect Size Specificationmentioning
confidence: 99%
See 1 more Smart Citation